Indian Ocean: Re-energising Trade Integration in IORA - Rana, Pradumna Bickram (2016)
The recent inaugural Indian Ocean Conference (IOC 2016) while well-timed and successful in projecting India’s soft power, failed to come up with concrete recommendations to re-energise trade within the region. This should be a key focus of IOC 2017.